(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article discusses the role of Smart resources in teaching Russian to students of the new generation of technical universities. Given the growing demand for multilingual professionals in technical fields, it’s important to understand how intellectual resources can improve language learning outcomes for Russian language learners. This article discusses the benefits and challenges of integrating Smart resources, such as language learning apps, online platforms and interactive multimedia tools, into the Russian language curriculum. The study also discusses the impact of smart resources on student engagement, motivation, and Russian language proficiency.